Analisis Hukum Pidana terhadap Manipulasi Keuangan dalam Bisnis Digital - Budi Handayani; Eko Budi Sariyono; Zabidin Zabidin; M. Aslam Fadli; Wahab Aznul Hidaya (Jurnal Multidisiplin Indonesia, 2026)
The rapid growth of the digital economy has transformed financial transactions through financial technology, electronic payment systems, and digital assets. Although these developments provide efficiency and convenience, they also create opportunities for financial manipulation and digital financial crimes. This study aims to analyze forms of financial manipulation in digital business, examine criminal law application toward perpetrators based on Indonesian regulations, and identify challenges in law enforcement. The research used a literature review method by analyzing academic journals, legal documents, and relevant regulations concerning digital financial crimes. The findings show that financial manipulation in digital business includes cyberlaundering, terrorism financing through digital platforms, transaction fraud, market manipulation, insider dealing, illegal fintech activities, and digital financial statement manipulation. These actions generally meet the elements of criminal offenses involving unlawful conduct, intent, causality, and financial losses. Criminal liability may apply to both individuals and corporations involved in or benefiting from such misconduct. However, law enforcement faces challenges related to transaction anonymity, cross-border activities, cryptocurrency use, and limited digital forensic capabilities. The study emphasizes the need to strengthen legal frameworks, enhance law enforcement capacity, and improve regulatory supervision to maintain the integrity of Indonesia’s digital business ecosystem.